A Comparison Between Core Biopsy and Imaging Techniques (Ultrasound and Mammography) In diagnosis of Breast Cancer in Slemani Breast Center - Hawramy, Taher Abdullah; Mohammed, Dara Ahmed; Ahmed, Hasan Abdullah (Kurdistan Journal of Applied Research, 2018)
Breast cancer is the global health problem. It is the highest prevalent site-specific cancer in women throughout the world and the most common reason of death in middle age women, following lung cancer. Up to 5% of breast cancers are caused by inheritance. Male breast cancer accounts for less than 1%. Mammography is the first imaging study to evaluate breast abnormalities, Ultrasound is particularly useful in young women with dense breasts. Core needle biopsy permits the analysis of breast tissue architecture and whether invasive cancer is present. To compare core needle biopsy and imaging, the accuracy of each modality for purpose of the diagnosis and their impact on preoperative planning before surgical treatment. A retrospective cohort study was performed in 70 cases of breast cancer during 2015-2017 at Slemani Breast Center/ Kurdistan region. Inclusion criteria any patient with diagnosed with breast cancer for whom core biopsy and imaging techniques (ultrasound and mammography) were done, Age 25 years and above. Exclusion criteria, a patient with breast mass who did not underwent: one of the two modalities, Age below 25 years, pregnant women. In the current study: mean age/year for the participants were Mean age = 51.34 year ± 12.85 SD), Sixty-nine cases were female and one male. By core biopsy (97.1%) is positive for malignancy. In this study: results about 34.28% of BIRADS V (ultrasound)lesions proved to be positive for malignancy by core biopsy, 1.43% of BIRADS V were negative for malignancy and the association was statistically highly significant, for BIRADS III lesions 17.14% were proved as positive for malignancy by core biopsy. About 45.7% of BIRADS V (mammography were positive for malignancy by core biopsy and the associations were found to be statistically highly significant and for BIRADS III 12.85% of lesions were positive for malignancy by core biopsy. There was a statistically significant association between radiological investigation(ultrasound, mammography) and histopathological finding (core biopsy).